Comparison of Herpes Simplex Virus 1 Strains Circulating in Finland Demonstrates the Uncoupling of Whole-Genome Relatedness and Phenotypic Outcomes of Viral Infection - Bowen CD; Paavilainen H; Renner DW; Palomäki J; Lehtinen J; Vuorinen T; Norberg P; Hukkanen V; Szpara ML (AMER SOC MICROBIOLOGY, 2022)
A majority of adults in Finland are seropositive carriers of herpes simplex viruses (HSV). Infection occurs at epithelial or mucosal surfaces, after which virions enter innervating nerve endings, eventually establishing lifelong infection in neurons of the sensory or autonomic nervous system. Recent data have highlighted the genetic diversity of HSV-1 strains and demonstrated apparent geographic patterns in strain similarity. Though multiple HSV-1 genomes have been sequenced from Europe to date, there is a lack of sequenced genomes from the Nordic countries. Finland's history includes at least two major waves of human migration, suggesting the potential for diverse viruses to persist in the population. Here, we used HSV-1 clinical isolates from Finland to test the relationship between viral phylogeny, genetic variation, and phenotypic characteristics. We found that Finnish HSV-1 isolates separated into two distinct phylogenetic groups, potentially reflecting historical waves of human (and viral) migration into Finland. Each HSV-1 isolate harbored a distinct set of phenotypes in cell culture, including differences in the amount of virus production, extracellular virus release, and cell-type-specific fitness. Importantly, the phylogenetic clusters were not predictive of any detectable pattern in phenotypic differences, demonstrating that whole-genome relatedness is not a proxy for overall viral phenotype. Instead, we highlight specific gene-level differences that may contribute to observed phenotypic differences, and we note that strains from different phylogenetic groups can contain the same genetic variations.IMPORTANCE Herpes simplex viruses (HSV) infect a majority of adults. Recent data have highlighted the genetic diversity of HSV-1 strains and demonstrated apparent genomic relatedness between strains from the same geographic regions. We used HSV-1 clinical isolates from Finland to test the relationship between viral genomic and geographic relationships, differences in specific genes, and characteristics of viral infection. We found that viral isolates from Finland separated into two distinct groups of genomic and geographic relatedness, potentially reflecting historical patterns of human and viral migration into Finland. These Finnish HSV-1 isolates had distinct infection characteristics in multiple cell types tested, which were specific to each isolate and did not group according to genomic and geographic relatedness. This demonstrates that HSV-1 strain differences in specific characteristics of infection are set by a combination of host cell type and specific viral gene-level differences.